Types of evidence used in anti-cartel investigations in El Salvador: standards established by the Administrative Review Chamber 2006-2019 - Arrieta de Carsana, Lilliam (2022)
The Competition Law of El Salvador of 2006 prohibits cartels between businessmen or economic operators, but since they are illegal agreements, generally carried out without leaving a material evidence trail, there is difficulty in proving their realization. This has generated multiple challenges related to the lack of forcefulness to justify the sanctions imposed, in the opinion of the affected companies. Many sanctions imposed by the Board of Directors of the Superintendency of Competition have been challenged in Contentious-Administrative proceedings, as it was the only jurisdiction before which appeals could be made during the period covered by this investigation. The methodology used in this article consisted of the analysis of all the resolutions in cases of cartels sanctioned by the competition authority, to extract the evidence that has allowed convicting; and in a second place, to examine the rulings of the Contentious Chamber of the Supreme Court of Justice of El Salvador to determine if they have confirmed the legality of the decisions of the competition authority or if they have established their illegality. The most relevant finding of this study, which can help economic operators to guide their actions within the framework of the Competition Law, is that the legality of all sanctions imposed in cartel cases has been confirmed.